(untitled) (TEST Antologia di Diritto Pubblico, 2024)
This contribution aims to reflect on both the usefulness and inactuality of Kelsen’s thought, delivered in the 1924 essay on public law and private law, moving from the specific perspective of comparative private law. After noting the importance of the Kelsenian critique with respect to the thesis of the ontological separation of public and private law, which is strongly rooted in European-Continental culture but absent in other experiences, the article reflects on the anti-ideological scope of Kelsenian thought, studying its implications for private law theory. In the last part, the contribution reasons about the changing contexts, which on the one hand make the “grand partition” increasingly and on the other hand attract the attention on the transformations of the concept of democracy – as originally employed by Kelsen – relevant for the analysis of private law relationships.